METHODOLOGICAL APPROACHES TO DETERMINING THE EFFECTIVENESS OF INNOVATIVE DEVELOPMENT OF ENTERPRISES (INNOVATIVE ECONOMY, 2021)
Voloshchuk V.R. METHODOLOGICAL APPROACHES TO DETERMINING THE EFFECTIVENESS OF INNOVATIVE DEVELOPMENT OF ENTERPRISESPurpose. The aim of the article is generalization of theoretical and methodological approaches to determining the effectiveness of innovative activities of the enterprise, the study of requirements, criteria and evaluation indicators.Methodology of research. General scientific and special methods are used in the course of research, in particular: monographic, analysis and synthesis – at research of concept of efficiency of innovative activity and approaches to its estimation; system analysis – in determining the state of innovation in industrial enterprises; tabular – for visual presentation of the analysed statistical data; abstract and logical – in determining the possible areas of innovative activity of enterprises of different sizes.Findings. There is an unstable trend of increasing the share of industrial enterprises that have implemented innovations (products and / or technological processes) in the total number of industrial enterprises, and an increase in the cost of innovative activity for the analysed period. It is determined that the best result is observed when implementing new or significantly improved low-waste, resource-saving technological processes, which indicates the dominance of process innovations.It is proved that the main source of funding for innovative activity is the own funds of enterprises, whose costs are growing annually and whose share is 87.7%. At the same time, most funds were spent on the purchase of machinery, software and equipment, iюeю on the renewal of material and technical base and modernization. There is an increase in the number of profitable enterprises, which indicates an increase in efficiency, as well as an increase in operating profitability and all activities of enterprises, but much higher rates are typical for micro and small enterprises, indicating their higher innovation activity and efficiency of modern development.Originality. Methodological approaches to determining the effectiveness of innovative development of enterprises have been improved, which, unlike existing ones, are based on incurred costs for innovation, volumes and sources of funding, reinvestment of profits, innovation activity, share of innovative products and increase profitability to substantiate possible directions of innovative development and implementation of measures to implement the results of research and development, taking into account the specifics and size of the business entities, the state and dynamics of the internal and external environment.Practical value. The use of generalized systematized methodological approaches to determining the effectiveness of innovative development of enterprises will allow to assess the results of the enterprise in each area of innovation based on the implemented innovative solutions in the current period and in the medium and long term.Key words: innovations, efficiency, technologies, products, development, enterprise, attractiveness, results, methodology.
Keywords: Key words; innovations; efficiency; technologies; products; development; enterprise; attractiveness; results; methodology.